2012
DOI: 10.1002/sim.5441
|View full text |Cite
|
Sign up to set email alerts
|

Frailty modeling of age–incidence curves of osteosarcoma and Ewing sarcoma among individuals younger than 40 years

Abstract: The Armitage—Doll model with random frailty can fail to describe incidence rates of rare cancers influenced by an accelerated biological mechanism at some, possibly short, period of life. We propose a new model to account for this influence. Osteosarcoma and Ewing sarcoma are primary bone cancers with characteristic age-incidence patterns that peak in adolescence. We analyze SEER incidence data for whites younger than 40 years diagnosed during the period 1975−2005, with an Armitage—Doll model with compound Poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…This approach may also be modified in several ways, including taking into account an expanding host tissue during, for example, puberty. 84 An important element is thus to combine models of carcinogenesis with a realistic understanding of individual differences, 6 , 84 , 85 to better understand features of population age-incidence rates.…”
Section: Interpretation Of Epidemiological Measuresmentioning
confidence: 99%
“…This approach may also be modified in several ways, including taking into account an expanding host tissue during, for example, puberty. 84 An important element is thus to combine models of carcinogenesis with a realistic understanding of individual differences, 6 , 84 , 85 to better understand features of population age-incidence rates.…”
Section: Interpretation Of Epidemiological Measuresmentioning
confidence: 99%
“…7 As frailty, the gamma-distribution, compound Poisson distribution, power-variance distribution, as well as other distributions, have been utilized. [8][9][10][11][12] Mathematically, the problem of modeling is stated as a best fitting of the hazard rates with observations using methods of regression analysis. The obtained models are useful when the utilized model parameters have apparent biological meaning and the estimated values of these parameters are consistent with the estimates presented by biological means.…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma and Ewing sarcoma also illustrate this age-related, second peak in incidence. Valberg et al suggested that an accelerated pubertal growth period may play a role in susceptibility to sarcomas during adolescence [ 20 ].…”
Section: Epidemiology Of Rmsmentioning
confidence: 99%